2022
DOI: 10.1097/sap.0000000000003410
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Elective Surgery Shutdown and Operative Experience for Graduating Plastic Surgery Independent Residents

Abstract: Introduction The initial wave of the COVID-19 pandemic led to a temporary shutdown of elective procedures. The purpose of this study is to evaluate how the elective surgery shutdown impacted case log numbers for graduating plastic surgery independent residents. Methods The Accreditation Council of Graduate Medical Education graduate self-reported case logs were retrospectively compiled for graduating independent track plastic surgery residents for the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…However, the findings in our study highlight that even with no significant change in case volume for those initial months, there was still an increase in cases after the peak of the pandemic. These findings were reflected in the procedure logs among plastic surgery residents, which demonstrate that despite the halt on surgeries, the pandemic did not impact the average resident case numbers, which continued on an upward trajectory, unlike what was observed for other specialties 36,37 . In fact, operative volume for plastic surgery residents remained higher than for orthopedic, neurosurgery, and general surgery, especially in the 2 years after March 2020 38 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the findings in our study highlight that even with no significant change in case volume for those initial months, there was still an increase in cases after the peak of the pandemic. These findings were reflected in the procedure logs among plastic surgery residents, which demonstrate that despite the halt on surgeries, the pandemic did not impact the average resident case numbers, which continued on an upward trajectory, unlike what was observed for other specialties 36,37 . In fact, operative volume for plastic surgery residents remained higher than for orthopedic, neurosurgery, and general surgery, especially in the 2 years after March 2020 38 .…”
Section: Discussionmentioning
confidence: 87%
“…These findings were reflected in the procedure logs among plastic surgery residents, which demonstrate that despite the halt on surgeries, the pandemic did not impact the average resident case numbers, which continued on an upward trajectory, unlike what was observed for other specialties. 36,37 In fact, operative volume for plastic surgery residents remained higher than for orthopedic, neurosurgery, and general surgery, especially in the 2 years after March 2020. 38 This evidence, along with what our data present, shows that institutions performing plastic surgery with and without residency programs have experienced a wave in plastic surgery procedures leading researchers to target the potential factors that may be driving this growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the effects of the pandemic on plastic surgery trainees' education; programs have had to shift to virtual learning, and residents performed fewer cases during the initial part of the pandemic. [9][10][11]15 The pandemic also affected resident wellness negatively. [12][13][14][15][16] However, despite the shutdown of elective and limitation of semielective cases, one study found that graduating independent residents in 2020 did not have significantly different case numbers than residents graduating before or after.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although studies have been done on the effect of the COVID-19 pandemic on plastic surgery trainees, few, (if any) have looked at the impact of a global pandemic on career choices of plastic surgery residents. 9–16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation